INCLUSIVE EDUCATION IN THE CONTEXT OF NATIONAL EDUCATION POLICY 2020: CHALLENGES AND STRATEGIES - Suokhrie, Kevizakielie; Kiewhuo, Kelhoulenuo (International Journal of Research -GRANTHAALAYAH, 2024)
Nothing can be more disastrous especially to disabled or for that any abled person, to be rejected or neglected by the families or peers or educational institutions etc. because he or she is different in some attributes whether in terms of gender, socio-economic background, language , caste , religion etc. The National Education Policy (NEP) 2020 strives to address the growing inequality aggravating country’s educational system. Inclusive education is a fundamental principle ingrained within NEP 2020, reflecting the commitment to provide quality education to every child, regardless of their background, abilities, or needs. However, towards achieving this goal there are certain issues, obstacles and challenges which need to be address through collaborative efforts of all. This paper attempt to highlight some of the key components of inclusive education as outlined in the NEP 2020, the potential challenges and strategies to implement NEP effectively for inclusiveness.